Conceptual Study of Shatkriyakala in Shuskashipaka (Dry Eye Syndrome) (International Journal of Ayurveda and Pharma Research, 2024)
Shushkakshipaka is considered as a Sarvakshi roga by Ayurveda acharyas. Among different Acharyas there is difference in opinion about the Dosha predominance of the disease. According to Susruth Acharya it is a Vataja disease; but Vagbhata describes it as a Vatapitta entity. Vata, Pitta and Rakta play major roles in the pathogenesis of Sushkakshipaka. The term Kriyakala refers to the progress of the disease, which helps to determine the treatment modalities to be given to make the Doshas in equilibrium. The Kriya Kala explained by Susrutha is having six stages, consider as Shadkriyakala. Here is an attempt to explain Shushkakshipaka in terms of Shadkriyakala so that one can understand the stage of the disease and decide the treatment to be given.